Analisis Pemangku Kepentingan dalam Pengembangan Kawasan Cagar Budaya sebagai Destinasi Wisata Kota Pontianak - Putu Ayu Vindytha Amanda Putri; Eko Budi Santoso (Department of Urban and Regional Planning, Diponegoro University, 2020)
Cultural heritage area in Pontianak needs to be preserved by developing and transforming it as a tourism destination. To do this development, it involves some groups of people or organization as acting stakeholders. The study aimed to identify their involvement and relationship in the management of and strategies for cultural heritage area in Pontianak City. The study used data which was analyzed using qualitative descriptive and stakeholder analysis methods. Then the results were incorporated into pentahelix modeling to explain further the roles and functions of each stakeholder. The results identified those acting stakeholders were of the Local Development Planning Agency of Pontianak City, the Youth, Sports and Tourism Agency of Pontianak City, the Pontianak City Tourism Promotion Board and the East Pontianak District Government with high influence and high importance. The community leaders such as historians and tourists were the stakeholders with low influence and high interests. Lastly, travel agents and tourism supporting business actors were the stakeholders with low influence and low interests.